(untitled) (Research, Society and Development, 2021)
Due to its easy dissemination and infection, COVID-19 created a delicate pandemic scenario that directly and indirectly influenced various sectors of society. Among these sectors, hospitals have become especially delicate work environments due to the difficulty in preventing and treating the disease. Assuming that the physical and emotional exhaustion caused by the intensification of working hours during the pandemic period contributes to physical and emotional exhaustion, this article aims to point out the impacts of the COVID-19 pandemic on the work of professionals from health. For this, an integrative review was carried out based on the consultation of texts found in the portal of journals VHL (Virtual Health Library) using the databases: LILACS (Latin American and Caribbean Literature in Health Sciences), MEDLINE and IBECS (Bibliographic Index Español en Ciencias de la Salud). In this review, 9 articles were included and read in full. Through this research, it can be seen that health professionals have increased daily risk due to the dangers generated by the pandemic scenario. The pressure of work in delicate circumstances results in physical and emotional stress, which can result in anxiety problems and impair the quality of work offered by these professionals. The improvement of factors such as infrastructure can reduce these problems and help improve professional well-being.